UiTM Vice-Chancellor presenting at the Oxford Academy for Education and Development, the United Kingdom - Wee, Roselind (UiTM Sarawak, 2015)
UiTM Vice-Chancellor, Tan Sri Dato’ Sri Sahol Hamid Abu Bakar was I invited by the Oxford Academy for Education and Development ’ (OAED), the United Kingdom to deliver a talk under the Leadership in Higher Education Programme held from 9,h to 13th December, 2014. In his paper entitled “University Leadership: A Case Study”, Tan Sri Dato’ Sri Sahol shared with senior leaders of universities all over the world on his experience of leading UiTM. Under the capable leadership of Tan Sri Dato’ Sri Sahol, UiTM has obtained many national and international awards such as the Most Entrepreneurial University Award for two consecutive years in 2012 and 2013 and the Best Islamic Finance Education Provider for the Global Islamic Finance Awards 2014 held in Dubai.